Vidal de la Blache, Ciência e Política: notas a partir do caso africano - Guilherme Ribeiro (Confins)
Thistext aims tohighlight the interestof Vidalde laBlachefor the African continent,from the standpointofapromoter ofFrench colonialism-thus revealingageographerengaged inpolitical,strategic andgeopolitical questions.